2009
DOI: 10.1186/1471-2334-9-187
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the impact of school closure on social mixing behaviour and the transmission of close contact infections in eight European countries

Abstract: BackgroundMathematical modelling of infectious disease is increasingly used to help guide public health policy. As directly transmitted infections, such as influenza and tuberculosis, require contact between individuals, knowledge about contact patterns is a necessary pre-requisite of accurate model predictions. Of particular interest is the potential impact of school closure as a means of controlling pandemic influenza (and potentially other pathogens).MethodsThis paper uses a population-based prospective sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
223
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(234 citation statements)
references
References 21 publications
9
223
1
Order By: Relevance
“…Chowell et al (2011) estimate that social distancing in Mexico in response to H1N1 reduced the spread of infection by roughly 1/3, which matches results in other contexts (Wu et al 2010, Hens et al 2009. Two works on gatherings in economics support these findings from epidemiology.…”
Section: Introductionsupporting
confidence: 64%
“…Chowell et al (2011) estimate that social distancing in Mexico in response to H1N1 reduced the spread of infection by roughly 1/3, which matches results in other contexts (Wu et al 2010, Hens et al 2009. Two works on gatherings in economics support these findings from epidemiology.…”
Section: Introductionsupporting
confidence: 64%
“…The possible closure triggers were a range of SAP thresholds (prevalence in children ages [5][6][7][8][9][10][11][12][13][14][15][16][17][18], based on the assumption that prevalence in this age group can be Figure 1 School closure policy pathway for high transmission scenarios. The full tree for the 0.5% school-age prevalence closure trigger is shown.…”
Section: School Closure Policies and The Decision Pathwaymentioning
confidence: 99%
“…A number of studies have quantified the impact of school closures on cumulative attack rates, but have not evaluated the social and economic costs of such policies [6,[8][9][10][11][12]. Some of these studies demonstrate school closures can have a significant impact on the basic reproduction number and on the overall spread of disease [4-7, 10, 13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…While there are few studies that have measured the impact of disease-related school closure on contact patterns [16,17], the impact of school holidays on contact patterns is better documented. Studies have shown that school pupils make considerably fewer social contacts each day during holiday periods than they do during term time [21,[23][24][25], and have predicted that the change in social contact patterns would lead to a reduction in the basic reproduction number of an influenza-like illness (ILI) of around 20-35% [21,25].…”
Section: Introductionmentioning
confidence: 99%